Clinical Relevance of Left Atrial Strain to Predict Recurrence of Atrial Fibrillation after Catheter Ablation: A Meta‐Analysis. Issue 5 (9th February 2016) - Ma, Xin‐Xin; Boldt, Leif‐Hendrik; Zhang, Yue‐Li; Zhu, Meng‐Ruo; Hu, Bing; Parwani, Abdul; Belyavskiy, Evgeny; Radha Krishnan, Aravind K.; Krisper, Maximilian; Köhncke, Clemens; Osmanoglou, Engin; Kropf, Martin; et al.
Abstract : Background: The purpose of this meta‐analysis was to analyze the clinical relevance of left atrial (LA) strain to predict recurrence of atrial fibrillation (AF) after catheter ablation (CA). Methods and Results: We searched in different databases (Medline, EMBASE, and Cochrane) prospective studies that analyzed LA strain before CA. Eight studies (2 with only paroxysmal AF and 6 with mixed population of paroxysmal and persistent AF) were included in the final analysis (total patient number = 686). Patients with recurrence of AF were principally characterized by lower LA strain in comparison with those without AF recurrence (mean 18.4% [range 8.8–24.5%] versus 25.3% [13.6–32.7%], weighted mean difference −4.89% [95% CI −5.83% to −3.95%], P < 0.001). In addition, receiver operating curves shown that LA strain was strongly associated with recurrence of AF after CA (weighted mean: AUC 0.798 [95% CI 0.700–0.943], cutoff 22.8% [18.8–30%], sensitivity 78% [65–86%], and specificity 75% [66–100%]). In line, these results were similar using LA strain with QRS‐analysis and P‐analysis as well as using different software package such as Echo‐Pac, QLab, TomTec, and VVI. Conclusion: In patients with AF candidate for CA, the analysis of the LA using LA strain could be of great usefulness to identify patients with high risk of AF recurrence. Nonetheless, further studies are needed to establish the clinical relevance of LA strain in patients with persistent AF.